A ironia, a pressuposição e o subentendido em Os Bruzundangas, de Lima Barreto - Matei, Maria Helena Corrêa da Silva (2019)
This postgraduate thesis in Portuguese language at Pontifícia Universidade Católica de São Paulo is in the line of research text and discourse in the oral and written form. It focuses on the textual and discursive elements present in the chronicles of Os Bruzundangas, de Lima Barreto. In these texts, irony is the guiding thread of the author's criticism of his society and, above all, involves the implicit content, detected, sometimes through the presupposition, and sometimes through the sub-understanding. In this context, the research questions which guide this study are: 1) how the implicit ones manifest themselves in the analysed chronicles?; 2) what relations can be established between the implicit and the ironic?; 3) In what way presupposition and the implied convey the implicit?; 4) To what extent the context allows the understanding of the implied? In order to answer these questions one must investigate the implicit in the chronicles of Lima Barreto published in Os Bruzundangas. As specific objectives one should: a) ascertain how the implicit manifests itself in the chronicles analyzed; b) identify the relations between implicit and irony; c) recognize the linguistic elements that bring the implicit ones, conveyed by the presupposition and the sub-understanding; d) identify the context that pervades each chronicle and allows the understanding of the implied. The theoretical contribution adopted consists primarily of Fargoni (1993), Fávero (2005, 2009), Neves (1992), Candido (1992) and Coutinho (1976). To deal with the chronicles: Nery (1998), Borges (2009) and Minois (2003). To deal with satire: Brait (2008), Moisés (2001), Perelman Tyteca (2014) and Sevcenko (2003) to deal with irony. In order to approach the presupposition adopted by Ducrot’s contributions (1972, 1981, 1987, 1991); in relation with the implicit, one sought Ducrot’s study (1987), and the notion of the context which adopted the theoretical approach offered by Charaudeau (2010) and van Dijk (2012). The development of this study justifies itself for having less research about Os Bruzundangas regarding the linguistic and extralinguistic. This research elucidates that the implicit elements are largely responsible for the construction of meaning, especially with regard to irony